Phytoremediation of heavy metals in soil and water: An eco-friendly, sustainable and multidisciplinary approach - Bhat, Shakeel Ahmad; Bashir, Omar; Ul Haq, Syed Anam; Amin, Tawheed; Rafiq, Asif; Ali, Mudasir; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Sher, Farooq (Elsevier, 2022)
Rapid industrialization, increased waste production and surge in agricultural activities, mining, contaminated irrigation water and industrial effluents contribute to the contamination of water resources due to heavy metal (HM) accumulation. Humans employ HM-contaminated resources to produce food, which eventually accumulates in the food chain. Decontamination of these valuable resources, as well as avoidance of additional contamination has long been needed to avoid detrimental health impacts. Phytoremediation is a realistic and promising strategy for heavy metal removal from polluted areas, based on the employment of hyper-accumulator plant species that are extremely tolerant to HMs present in the environment/soil. Green plants are used to remove, decompose, or detoxify hazardous metals in this technique. For soil decontamination, five types of phytoremediation methods have been used viz. phytostabilization, phytodegradation, rhizofiltration, phytoextraction and phytovolatilization. Traditional phytoremediation methods, on the other hand, have significant limits in terms of large-scale application, thus biotechnological efforts to modify plants for HM phytoremediation ways are being explored to improve the efficacy of plants as HM decontamination candidates. It is relatively a new technology that is widely regarded as economic, efficient and unique besides being environment friendly. New metal hyperaccumulators with high efficiency are being explored and employed for their use in phytoremediation and phytomining. Therefore, this review comprehensively discusses different strategies and biotechnological approaches for the removal of various HM containments from the environment, with emphasis on the advancements and implications of phytoremediation, along with their applications in cleaning up various toxic pollutants. Moreover, sources, effects of HMs and factors affecting phytoremediation of HMs metals have also been discussed.
Keywords: Heavy metals; Nanotechnology; Phytoextraction and genetic engineering; Phytoremediation; Sustainability; Waste management